Comprehensive lipoprotein and glycoprotein characterization in rheumatoid arthritis plasma and association with clinical markers - Tsezou, Konstantina Ismini; Ghorasaini, Mohan; Verhoeven, Aswin; Iliou, Aikaterini; Benaki, Dimitra; Vlachoyiannopoulos, Panayiotis G.; Giera, Martin; Mikros, Emmanuel (Frontiers in Molecular Biosciences, 2025)
IntroductionRheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation and pain. This study investigates plasma lipoprotein and glycoprotein profiles in RA patients to identify clinically relevant markers for disease monitoring.MethodsLipoprotein composition and subfractions were analyzed in plasma from 161 RA patients and 46 controls using proton nuclear magnetic resonance (1H NMR) spectroscopy (Lipoprotein Subclass Analysis (B.I.LISA) platform) along with N-acetylglycoprotein signals GlycA and GlycB. Lipoprotein subclasses and glycoproteins in RA and disease-modifying anti-rheumatic drug (DMARD)-naive RA patients were compared to controls, and comprehensive profiles were evaluated in activity and remission. Correlations with disease activity score (DAS28), inflammation marker C-reactive protein (CRP), and Visual Analogue Scale (VAS) of pain were assessed using regression models, adjusting for age, gender, and CVD.ResultsRA patients exhibited a distinct lipoprotein and glycoprotein profile, with increased triglycerides, cholesterol, apolipoproteins (A1, A2, B100), and changes in LDL, HDL, GlycA, and GlycB. Glycoproteins were significantly higher in DMARD-naive RA (AUC ≈ 0.9) validating these NMR signals as biomarkers of inflammation. Patients in remission had higher small dense HDL and lower LDL-triglycerides than those with high disease activity. VAS correlated with LDL-triglycerides, while DAS28 correlated with small dense LDL-triglycerides and glycoproteins, inversely with large LDL, small HDL lipids. H4A1 alone characterizes RA remission (AUC ≈ 0.8).ConclusionLipoprotein profiles in RA correlate with disease activity, inflammation, and pain. Large HDL, intermediate LDL and glycoproteins serve for RA monitoring as well as potential molecular markers of pain.